(untitled) (Research, Society and Development, 2025)
Social exclusion and the stigma associated with individuals diagnosed with mental disorders constitute not only barriers to social coexistence but also forms of denying their existence as beings-in-the-world. The label imposed by diagnosis, often reinforced by biomedical discourses and dominant social culture, compromises these individuals’ freedom, identity, and right to be, reducing them to the clinical condition attributed to them. In this context, understanding the impact of stigma on the constitution of subjectivity becomes essential for developing psychological practices that are more ethical, humanized, and open to the uniqueness of each existence. This study aims to reflect, in light of existential phenomenology, on how stigma and exclusion impact the subjectivity and being-with-others of individuals diagnosed with mental disorders, while also considering how these subjects perceive themselves and are perceived by the world. This is a bibliographic study based on the analysis of academic works published between 2015 and 2025, as well as classical texts in the field. The search was conducted using platforms such as SciELO, Google Scholar, PEPSIC, and CAPES Journals, employing strategic terms related to the topic, such as “stigma,” “mental disorders,” “existential phenomenology,” and “subjectivity”. The results show that clinical listening grounded in an existential-phenomenological perspective makes it possible to deconstruct the reductionist view imposed by diagnosis, allowing the subject to be recognized beyond the label that confines them. When internalized, stigma weakens self-experience and compromises one’s way of being-in-the-world, generating exclusions that go beyond the social sphere and reach an ontological level — the very sense of existence. The analysis also indicates that a clinical stance based on openness to otherness fosters the recovery of authenticity and the recognition of human dignity, breaking with dehumanizing practices that reinforce the marginalization of psychological suffering. It is concluded that psychiatric diagnosis, when used in a labeling and decontextualized manner, tends to produce exclusion and stigmatization, distancing the professional from a comprehensive understanding of the subject. Therefore, it becomes essential to adopt an ethical, humanized, and phenomenologically oriented stance that recognizes the person in their totality and respects their freedom to be. Ethics, in this sense, must permeate all psychological practice, sustaining a mode of listening that is committed to the other in their singularity and to the promotion of a more authentic, free, and dignified existence.